Formaldehyde from methanol a design report - Adriano, Zenaida S. (College of Engineering, 1961)
This proposed formaldehyde plant will require a minimum of 27 pieces of principal process-equipment. The design is for a daily output of 20 tons per day of 37% formaldehyde, stabilized with 8% of methanol, according to standard product specifications. The minimum land area required is 114,200 sq. ft. An L-shaped building is recommended. The cost analysis of the proposed plant has indicated the complete feasibility of the design. It will require an initial capital investment of P3,146,953.00, and will realize a profit of 304,048.00 after taxes. If operating at the design capacity of 20 tons per day, and with a maximum sales volume of P1,370,000. pay-out time will be four and one-half years.